Detection of zika virus disease caused by the Asian lineage of the zika virus at Kenya's Lamu island - Gathii Kimita; John Collins; Beth Mutai; Esther Omuseni; Clement Masakhwe; Stephen Ocholla; Allan Lemtudo; George Awinda; Rachel Githii; Gerald Kellar; John Waitumbi (International Journal of Infectious Diseases)
Objectives: We report the first confirmed cases of Zika virus (ZIKV) disease (ZVD) in Kenya and provide the associated genomic sequences. Methods: The study is part of a prospective febrile illness surveillance study in Kenya. A cluster of ZVD cases was identified in patients with fever presenting at King Fahd Referral Hospital, Lamu Island. Clinical signs resembled those caused by dengue or malaria and included fever, chills, muscle and joint pains, and headache. The Biofire Film Array Global fever panel (BioFire Diagnostics, UT, USA) identified ZIKV in three of five blood samples. RNA extracted from plasma was used for sequence library preparation and subsequent viral enrichment using the VirCapSeq-VERT probe set designed at the Center for Infection and Immunity, Columbia University. Enriched libraries were sequenced on the NextSeq 2000 (Illumina, San Diego, CA, USA). Assembled genomes were classified into lineages and a spatio-temporal phylogeny inferred with Nextstrain v8.5.3. Results: Assembled genomes produced contigs covering between 3363 and 10,950 nt that mapped to the Asian lineage of ZIKV and branched with genomes from India. Mutation profiling revealed viral strains with potentially enhanced transmission and immune evasion capabilities. Conclusions: The presence of the more transmissible Asian lineage ZIKV that has previously caused large outbreaks of ZVD in the Americas raises significant public health concern.